Energy Minimization by Selecting Appropriate Modulation and Coding Scheme for MB-OFDM UWB Systems - Chihi, Houda; Zaeem, Reza Mahin; Bouallegue, Ridha (Proceedings / International Conference on Advanced Information Networking and Applications, 2016)
Due to the exploding evolution of wireless communication systems, energy efficiency (EE) becomes the concern of many researches. In this context, we examine this metric into multiband orthogonal frequency division multiplexing ultra wideband (MB-OFDM UWB) systems. Indeed, the focus is about investigating a cross-layer design based on the joint combination between data link layer through the hybrid automatic repeat request (HARQ) protocol and the physical layer across modulation and coding scheme (MCS) towards the MB-OFDM UWB (MB-UWB) systems. The objective is to find the suitable MCS allowing energy minimization. Nevertheless, the idea is about determining the most energy efficient mode selection providing total energy consumption per throughput diminishing. Next, a theoretical framework displaying the throughput of different MCS derivation is introduced following a specific energy consumption model adoption. Numerical results reveal the most energy efficient MCS scheme ensuring energy expenditure diminishing.